The differential identity activation & integration Mechanism (DIAIM): A model linking female businesspersons’ identity integration and identity activation to negotiation - TAN, Yi Wen (Institutional Knowledge at Singapore Management University, 2017)
Women play an important role in business management (female businesspersons) but yet they face constraints in the workplace, such as in negotiations. As female businesspersons seem to be facing seemingly conflicting gender and business identities, the level of the integration between these identities, as captured by the construct gender-professional identity integration (G-PII), can be a critical factor that influences female businesspersons in negotiations. It is expected that the level of G-PII influences female businesspersons’ negotiation behaviors when their different identities (i.e., female identity, business identity or dual identities) are activated. Hence, a DIAIM model that depicts how female businesspersons with different levels of G-PII may react to single versus dual identity primes behave is proposed. It is then applied to study female businesspersons in mixed-motive negotiations. A pilot study was conducted to develop an identity priming task for female businesspersons’ identity frame switching. Results of the pilot study showed that female businesspersons with high G-PII exhibited a reversed assimilation effect while low G-PIIs exhibited a reversed contrast effect. In the main study, the propositions in the DIAIM were tested on female businesspersons’ negotiation behaviors. Results showed that identity cues moderated female businesspersons’ G-PII to affect their competition and personal negotiation outcomes, hence it provided some support to the DIAIM model. Overall, this research went beyond what past research had found on how people’s single identity activation and provided some evidence for the simultaneous activation of multiple identities.